Structural and evolutionary analyses of the mitochondrial genome of Spuriopimpinella brachycarpa - Jun Han; Wenbo Xu; Huanxi Yu; Yun Han; Ming Zhu (Frontiers in Plant Science)
IntroductionSpuriopimpinella brachycarpa (Kom.) Kitag., a member of the Apiaceae family, is a perennial aromatic herb native to Northeast Asia with applications in culinary and traditional medicine. Despite its significance, most studies on S. brachycarpa have primarily focused on its phytochemical properties, with limited insights into its molecular and genomic characteristics.MethodsThis study presents the sequencing and assembly of the mitochondrial genome (mitogenome) of S. brachycarpa using second- and third-generation high-throughput sequencing technologies. Comprehensive analyses were performed on its structural organization, RNA editing sites, relative synonymous codon usage (RSCU), and repeat sequences. Comparative analyses with closely related species were also conducted.ResultsThe mitogenome exhibited a multi-branched structure, with a total length of 523,512 bp and a GC content of 43.37%. Annotation revealed 30 unique protein-coding genes, 21 tRNA genes, and three rRNA genes. Comparative analysis indicated that the S. brachycarpa mitogenome contains structural variations but shares collinear features with other Apiaceae species. We identified 618 potential RNA editing sites involving C-to-U conversions and discovered 59 homologous fragments between the mitogenome and plastome, comprising 8.13% of the mitogenome.DiscussionThese results enrich the genomic database of Apiaceae, providing valuable insights into the evolutionary relationships and genetic diversity within the family.